Real-time imaging of the intracellular glutathione redox potential - Gutscher, Marcus; Pauleau, Anne-Laure; Marty, Laurent; Brach, Thorsten; Wabnitz, Guido H.; Samstag, Yvonne; Meyer, Andreas; Dick, Tobias P. (Nature methods, 2008)
Dynamic analysis of redox-based processes in living cells is now restricted by the lack of appropriate redox biosensors. Conventional redox-sensitive GFPs (roGFPs) are limited by undefined specificity and slow response to changes in redox potential. In this study we demonstrate that the fusion of human glutaredoxin-1 (Grx1) to roGFP2 facilitates specific real-time equilibration between the sensor protein and the glutathione redox couple. The Grx1-roGFP2 fusion protein allowed dynamic live imaging of the glutathione redox potential (E(GSH)) in different cellular compartments with high sensitivity and temporal resolution. The biosensor detected nanomolar changes in oxidized glutathione (GSSG) against a backdrop of millimolar reduced glutathione (GSH) on a scale of seconds to minutes. It facilitated the observation of redox changes associated with growth factor availability, cell density, mitochondrial depolarization, respiratory burst activity and immune receptor stimulation.
Gesehen am 25.06.2021